ANALISIS KAJIAN STILISTIKA DAN MAKNA PADA PUISI “MATA HITAM” KARYA W.S. RENDRA - Elsa Novianti (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2022)
Literary works are expressions that convey ideas and ideas conveyed by an author. Literary works in the form of poetry discuss a lot about life such as feelings, education, economics, social, politics and culture. This study aims to determine the meaning of the poem Mata Hitam by W.S. Rendra. This study uses a stylistic approach based on the theory of Wallek & Warren, 1995: 229 and Munir, S, & Mulyono, 2013: 2. This study uses qualitative methods and content analysis. The source of data in this study is the poem Mata Hitam by W.S. Rendra. The result of this research is to know the stylistic and meaning contained in the poem through sentence structure, figure of speech, imagery, pattern, and rhyme. Every love poem by W.S. Rendra has different meanings of love and always ends happily.